Utilization of Waste Clay–Diatomite in the Production of Durable Mullite-Based Insulating Materials - Svetlana Ilić; Jelena Maletaškić; Željko Skoko; Marija M. Vuksanović; Željko Radovanović; Ivica Ristović; Aleksandra Šaponjić (Applied Sciences, 2025)
Microstructural, mechanical and qualitative phase identification of durable mullite-based ceramics obtained by utilization of waste clay–diatomite has been studied. Mullite-based ceramics were fabricated using waste clay–diatomite from the Baroševac open-cast coal mine, Kolubara (Serbia). The raw material consists mainly of SiO2 (70.5 wt%) and a moderately high content of Al2O3 (13.8 wt%). In order to achieve the stoichiometric mullite composition (3Al2O3-2SiO2), the raw material was mixed with an appropriate amount of Al(NO3)3·9H2O. After preparing the precursor powder, the green compacts were sintered at 1300, 1400 and 1500 °C for 2 h. During the process, rod-shaped mullite grains were formed, measuring approximately 5 µm in length and a diameter of 500 nm (aspect ratio 10:1). The microstructure of the sample sintered at 1500 °C resulted in a well-developed, porous, nest-like morphology. According to the X-ray diffraction analysis, the sample at 1400 °C consisted of mullite, cristobalite and corundum phases, while the sample sintered at 1500 °C contained mullite (63.24 wt%) and an amorphous phase that reached 36.7 wt%. Both samples exhibited exceptional compressive strength—up to 188 MPa at 1400 °C. However, the decrease in compressive strength to 136 MPa at 1500 °C is attributed to changes in the phase composition, the disappearance of the corundum phase and alterations in the microstructure. This occurred despite an increase in bulk density to 2.36 g/cm3 (approximately 82% of theoretical density) and a complete reduction in open porosity. The residual glassy phase (36.7 wt% at 1500 °C) is probably the key factor influencing the mechanical properties at room temperature in these ceramics produced from waste clay–diatomite. However, the excellent mechanical stability of the samples sintered at 1400 and 1500 °C, achieved without binders or additives and using mined diatomaceous earth, supports further research into mullite-based insulating materials. Mullite-based materials obtained from mining waste might be successfully used in the field of energy-efficient refractory materials and thermal insulators. for high-temperature applications